Glucose curve morphology and peak time as biomarkers of metabolic health - Zahra Fatahimeiabadi; Jehu Narh Apaflo; Sudip Bajpeyi (American Journal of Physiology-Endocrinology and Metabolism, 2026)
Participants in biphasic groups showed better glucose tolerance than monophasic participants. Participants in early-peak groups showed better glycemic control and energy metabolism than late-peak participants. Glucose peak time demonstrates a stronger discriminative index of metabolic health than glucose curve morphology. Glucose peak time could serve as a useful biomarker of the OGTT for identifying potential diabetes risks.